Economic burden of chronic obstructive pulmonary disease and post-tuberculosis sequelae in low- and middle-income countries: a database compiled from a systematic review and meta-analysis - Fabrizio Tediosi; Klaus Reither; Olivia Keiser; Alexandra Walker; Yuling Lin; Marguerite Batta; Sierra Ottilie-Kovelman; Anna Duchenko; Curdin Brugger; Robert S Wallis; Marina Antillon (BMJ Publishing Group, 2024)
Background Chronic obstructive pulmonary disease (COPD) and tuberculosis (TB) impose a substantial economic burden globally. This systematic review summarised the evidence on the costs of COPD, including post-TB diseases in low- and middle-income countries.Methods A systematic review was conducted and studies published between 1 January 2013 and 28 March 2022 (the date of the search) were identified using various electronic databases without language restrictions. Titles, abstracts and full texts were screened in duplicate and data were extracted and verified by reviewers. Eligible studies were categorised as cost analysis and/or economic burden studies, and costs were converted to 2021 United State dollar. Meta-analysis was conducted on the costs of hospitalisations, medication and outpatient visits.Results 128 cost studies and 65 economic burden studies were included in this review. The data collected are presented in the Cost Database of COPD and Post-TB (CD-CPTB). The majority of studies were from Asia, Eastern Europe and Latin America, with a few from other middle-income countries. There were extremely limited data on the costs of post-TB sequelae and only a few studies were from Africa (n=6) and low-income (n=5) countries. The direct medical costs of COPD ranged from $26 per hospitalisation in India to $2694 per year per patient with severe disease in Mexico, while the costs of acute exacerbation of COPD ranged from $137 to $4207 per exacerbation with both the minimum and maximum costs occurring in Turkey. The costs were lower in lower middle-income countries compared with upper middle-income countries. Finally, considerable economic burden was attributable to smoking and air pollution.Conclusion The review and the CD-CPTB database give a thorough snapshot of the current evidence of the costs and economic burden of COPD and post-TB diseases. Future research is needed to investigate the economic impact after TB treatment and should be prioritised in Africa and low-income countries where there has been a lack of data collection.Protocol registration number CRD42022326609.